(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article reveals the nature and significance of the interaction between the operational units of the internal affairs bodies to combat narcotic drugs and other industry services and bodies carrying out activities to interact with the population. The article analyzes the concept, forms and stages of relationships, organizational and managerial aspects, the author’s definition of the concept of “activities of other industry services and public cooperation in the fight against drugs of operational units of internal affairs bodies”, as well as opportunities are formed as its effectiveness increases. The work uses a complex of general scientific and special scientific methods of cognition, including such methods as the systematic method, synthesis, analysis, induction and other methods of scientific research. The scientific novelty lies in a comprehensive analysis of the nature and content of interaction between operational units of internal affairs bodies with other industry services and the public in the fight against drugs. The main conclusion of the study is that the levels, forms and areas of cooperation between operational units of internal affairs bodies with other industry services and the public in the fight against drugs are closely related to each other and together constitute its main content.